HUBUNGAN MOTIVASI SISWA MEMILIH SEKOLAH TERHADAP PERENCANAAN ARAH KARIER - Isra, Fauzi; Prayitno, Prayitno; Karneli, Yenni (KOPASTA : Jurnal Program Studi Bimbingan Konseling, 2020)
Basically, education is part of a long way trip on to career. Education is also a major element of one's efforts in preparing to enter the world of occupations. Suitability of employment with the state itself is believed, will bring them to a better life in the future. More specifically, for high school students, a decision on the selected type of education has direct implications for the career, office or aspired to a career after completing his studies at the level of education which he passes. This research were aims at reveal and explain the relationship between student motivation in school to learn to plan a career direction. Hypotheses were proposed, there is a correlation of school students motivation for students planning a career direction.